Einstein vs. Bergson An Enduring Quarrel on Time - Campo, Alessandra; Gozzano, Simone (Transcodification: Arts, Languages and Media, 2021)
On 6 April 1922, Einstein met Bergson to debate the nature of time: is the time the physicist calculates the same time the philosopher reflects on? Einstein claimed that only scientific time is real, while Bergson argued that scientific time always presupposes a living and perceiving subject. On that day, nearly 100 years ago, conflict was inevitable. Is it still inevitable today? How many kinds of time are there?